Prevalence of anti-Hepatitis E IgG analyzed in sera through three commercial kits - Padilla-Sanabria, Leonardo (Universidad y Salud, 2020)
Introduction: Hepatitis E virus (HEV) is a nonenveloped, RNA virus. HEV genotypes 3 and 4 are considered zoonosis transmitted by contaminated water and/or food. The presence of antibodies against this virus have not been described in communities inhabiting the “Coffee Axis” region of Colombia. Objective: To determine the prevalence of anti-Hepatitis E IgG in serum samples analyzed in a clinical laboratory from the Colombian Coffee Axis. Materials and methods: 90 serum samples from patients treated at a clinical laboratory in the city of Armenia (Quindio) were analyzed and compared through three different methods that characterize antibodies. Results: The Mikrogen recomWell ELISA kit (IgG anti-HEV) identified two positive sera (2.2%). The Diapro HEV IgG ELISA (version ULTRA®) test registered a false positive sample (1.1%). The Mikrogen recom Line HVE western blot assay detected 4 positive samples (4.4%). Conclusions: Depending on the commercial kit used, the prevalence of anti-HEV IgG antibodies fluctuated between 0% to 4.4%, which demonstrates that the virus is circulating and that a possible infectious cycle in this region exists.